A Naked Seed: Platonism, Stoicism, or Agriculture in 1Cor 15,37? - Cook, John Granger (Zeitschrift für die neutestamentliche Wissenschaft, 2020)
Paul’s expression in 1Cor 15,37, γυμνὸς κόκκος, has nothing whatsoever to do with a Platonist naked soul or Stoic imagery of sowing and seeds. The context itself indicates that an immortal Platonic soul is not the reference of γυμνὸς κόκκος. The Platonist texts and the Stoic imagery of sowing and seeds do not resemble Paul’s affirmations in 1Cor 15,37. Instead, texts from Greek biology and agriculture are far more illuminating. The naked seed of 1Cor 15,37 are a metaphor for sown dead bodies. The context and comparative texts indicate Paul’s fundamental analogy: the naked seed is to the sown body as the plant body is to the body that will be.